2018
DOI: 10.3390/ijms19082431
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Xenograft Models for Endometrial Cancer Research

Abstract: Endometrial cancer (EC) is the most common malignancy of the genital tract among women in developed countries. Recently, a molecular classification of EC has been performed providing a system that, in conjunction with histological observations, reliably improves EC classification and enhances patient management. Patient-derived xenograft models (PDX) represent nowadays a promising tool for translational research, since they closely resemble patient tumour features and retain molecular and histological features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…With the rapid development of genotype-based individualized targeted therapies, preclinical trials using in vitro and in vivo models are essential in elucidating gene function and validating potential therapeutic targets 8 . In the last decade, a series of patient-derived xenograft (PDX) models have been developed and have rapidly gained favor over use of conventional cell lines as a preclinical drug screening platform, including for pancreatic cancer 9 , 10 , colorectal cancer 11 13 , hepatocellular carcinoma 14 , 15 , breast cancer 16 , 17 , epithelial ovarian cancer 18 , esophageal cancer 19 , 20 , and other cancers 21 23 . These PDX-based preclinical models accurately recapitulate the pathological and molecular characteristics of corresponding individual tumors, better reflecting patient heterogeneity and clinical diversity.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of genotype-based individualized targeted therapies, preclinical trials using in vitro and in vivo models are essential in elucidating gene function and validating potential therapeutic targets 8 . In the last decade, a series of patient-derived xenograft (PDX) models have been developed and have rapidly gained favor over use of conventional cell lines as a preclinical drug screening platform, including for pancreatic cancer 9 , 10 , colorectal cancer 11 13 , hepatocellular carcinoma 14 , 15 , breast cancer 16 , 17 , epithelial ovarian cancer 18 , esophageal cancer 19 , 20 , and other cancers 21 23 . These PDX-based preclinical models accurately recapitulate the pathological and molecular characteristics of corresponding individual tumors, better reflecting patient heterogeneity and clinical diversity.…”
Section: Introductionmentioning
confidence: 99%
“…This approach would help to build upon unique advantages of PDOs in comparison to other valuable disease models such as patient derived xenografts (PDXs). The latter are still considered as "gold standard" to assess tumourigenic potential of any cancer type, and have been successfully created for gynaecological malignancies [110,111]. However, despite providing clear benefits as in vivo experimental models [112], PDXs do have limitation of xeno-tissue environment.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Thus, PDX models are not only anticipated to capture both the intra-and inter-tumor heterogeneity of endometrial carcinoma, as has been previously demonstrated for breast, lung and pancreatic cancer, but also to faithfully reproduce clinical responses to chemotherapy [16,17]. Critically, orthotopic PDX models, i.e., where primary biopsies are implanted into the organ/microenvironment of origin, are proposed as a superior paradigm of clinical disease compared with subcutaneous PDX [18][19][20]. However, a major caveat of the orthotopic approach, particularly with patient-derived material, is longitudinal and spatio-temporal monitoring of not only disease development and characterization but also for further intervention studies.…”
Section: Introductionmentioning
confidence: 95%